Understanding ion-induced assembly of cellulose nanofibrillar gels through shear-free mixing and in situ scanning-SAXS. Issue 17 (26th July 2021) - Rosén, Tomas; Wang, Ruifu; He, HongRui; Zhan, Chengbo; Chodankar, Shirish; Hsiao, Benjamin S.
Abstract : Using in situ X-ray scattering in a shear-free mixing experiment, the time-resolved ion-induced gel transition of cellulose nanofibrils is studied. Abstract : During the past decade, cellulose nanofibrils (CNFs) have shown tremendous potential as a building block to fabricate new advanced materials that are both biocompatible and biodegradable. The excellent mechanical properties of the individual CNF can be transferred to macroscale fibers through careful control in hydrodynamic alignment and assembly processes. The optimization of such processes relies on the understanding of nanofibril dynamics during the process, which in turn requires in situ characterization. Here, we use a shear-free mixing experiment combined with scanning small-angle X-ray scattering (scanning-SAXS) to provide time-resolved nanoscale kinetics during the in situ assembly of dispersed cellulose nanofibrils (CNFs) upon mixing with a sodium chloride solution. The addition of monovalent ions led to the transition to a volume-spanning arrested (gel) state. The transition of CNFs is associated with segmental aggregation of the particles, leading to a connected network and reduced Brownian motion, whereby an aligned structure can be preserved. Furthermore, we find that the extensional flow seems to enhance the formation of these segmental aggregates, which in turn provides a comprehensible explanation for the superior material properties obtained in shear-free processes used for spinning filaments from CNFs. This observation clearly highlights the need for different assembly strategies depending on morphology and interactions of the dispersed nanoparticles, where this work can be used as a guide for improved nanomaterial processes.